Developing Problem-Based Learning Modules on Petroleum Materials in Chemistry Learning - Fauziah Ahmad; Murtihapsari Murtihapsari; Yunita Pare Rombe (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2023)
The aim of this study is to investigate how to develop, validity, and practicality levels from the PBL-based module. The research is based on Research & Development (R&D) with a modified 4-D development model to 3-D covering define, design, and development stages. Data collection tools include observation, validation, worksheet, and questionnaires of students’ responses to the chemistry modules. Based on the study results, it was identified that the modules developed to determine criteria eligibility, practicality, and response students of Problem-Based Learning on petroleum material. The material and media experts' validation tests showed 0.851 and 0.726 (valid), respectively. The average practically percentage of modules for students is 77.52% with very practical criteria. The development of PBL-based chemistry modules on chemistry and the application of petroleum is expected to help students in learning chemistry.